Safety and outcomes of percutaneous nephrolithotomy in the supine position: a single-centre experience - Muppirala, Lakshmi Ramesh; Bathalapalli, Ravi Theja; Jagirdar, S. Faisal Yazdani; Gaddam, Yaswanth Kumar (International Journal of Research in Medical Sciences, 2024)
Background: The technique of percutaneous nephrolithotomy (PCNL) was initially introduced by Fernström and Johansson in 1976, with the patient positioned in the prone position. Valdivia's study showed that PCNL performed in the supine position had comparable results and complications to PCNL performed in other positions, while also offering potential benefits in terms of ergonomics and anesthesia administration Methods: A prospective interventional study was conducted at Narayana medical college and hospital, a tertiary care centre in Nellore, AP, India between January 2023 to May 2024. Patients with sepsis, blood coagulation abnormalities, bifid pelvicalyceal system, pediatric population were excluded Results: The median operative duration was 85.59±12.733 min, and the median duration of X-ray exposure was 12 min. The mean (SD) volume of irrigant fluid was 32.9 liter. One puncture in 73 (89.0%) while 9 (11%) needed two punctures. the mean (SD) reduction in hemoglobin level was 0.8±0.13 mg/dl, with no patients requiring a transfusion. 77 patients had no or <3 mm residual fragments, resulting in a stone free rate of 93.9%. of the five patients with residual stones. There were complications in 13 patients (15.85%); 6 (7.31%) had a persistent urine leak for >24 h after nephrostomy removal Conclusions: Despite the statistically insignificant results, the outcomes were obviously improved and demonstrated to be comparable to other facilities, with a high stone-free rate and low complications, and post-op length of hospital stay. As a result, the efficacy and safety of supine PCNL in our center were confirmed.